Measles – are we dealing with a new epidemy in Poland? - Rutkowski, Maciej; Świerszcz, Łukasz; Roszkowska, Anna; Taracha, Anna; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2017)
Introduction: In the past few years, a group of parents avoid mandatory vaccination of children has increased. One of the effects of this action is increasing incidence of measles among unvaccinated people. The knowledge of current trends enables us to design and develop education programs for parents and to deny the distortion inherent myths about vaccinations. Objective: The objective of the research is the analysis of the current epidemiological situation of measles incidence. Material and method: Research material used for the analysis of measles incidence was taken from reports „Choroby zakaźne i zatrucia w Polsce w 2016 roku” and „Szczepienia ochronne w Polsce w 2016 roku” prepared by National Institute of Hygiene. Material was analysed by epidemiological descriptive method. Results: In 2007 measles vaccination coverage in Poland was 99,7% and in 2014 it was only 95,5%. In analysed period percentage of incidence among unvaccinated population was 54%, among vaccinated was 18% and in 28% there was no information about vaccination. Furthermore, the greatest incidence occurs among unvaccinated population of children aged 0-4 years, which one is particularly exposed to severe complications. Conclusion: General trends show that there has been a considerable decrease of measles vaccination coverage in Poland. Moreover, more than half of cases of measles incidence concern unvaccinated population. This indicates the necessity of implementation of new education programs directed to parents and need to intensify efforts to eliminate harmful myths regarding vaccination.